HUBUNGAN TIPE KEPRIBADIAN DENGAN PILIHAN KARIER PADA SISWA KELAS X SMKN 1 SALATIGA - Novian Dwi Cahyonugrahanto; Tritjahjo Danny Soesilo; Maya Rahadian Septiningtyas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In life, everyone must of course recognize and know their true identity. After recognizing and knowing about one's identity, humans will know the abilities they possess. This ability is what humans will use to develop and continue their lives, especially in terms of work or career. Choosing a career is a very crucial decision in life, because if the choice is not appropriate it will have a bad impact on life. Therefore, career selection must be based on personality type. This research was conducted with the aim of finding out the significance of the relationship between personality type and career choices of class X students at SMK Negeri 1 Salatiga. The subjects in this research were class X students of SMK Negeri 1 Salatiga, totaling 205 respondents who were used as samples. The data collection method used is using questionnaires. The analysis technique used is the Contingency Coefficient with the help of the SPSS application. 20. Based on the research results showing that there is a significant relationship between Personality Type and Career Choice, it can be proven by the Asimp.Sig value of 0.000 < 0.05, it can be concluded that H1 is accepted. This can also be interpreted that a person's personality type has a correlation with a person's career choice. The approximate significance (P-Value) value of 0.000 is smaller than 0.05 (0.000 < 0.05), so it can be concluded that there is a significant relationship between Personality Type and students' Career Choices. The correlation value obtained is 0.569, which means that the strength of the relationship between personality type and career choice is sufficient.